PENGARUH PERENCANAAN PAJAK, KEWAJIBAN MORAL DAN PEMERIKSAAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN DENGAN DIGITALISASI ADMINISTRASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Safri Yetmi, Yosi (Universitas Prof.Hazairin,SH Bengkulu, 2023)
This research aims to determine the influence of Tax Planning, Moral Obligations, and Tax Audits on Corporate Taxpayer Compliance with the Digitalization of Tax Administration as a Moderating Variable in companies located in the Tangerang Regency area. The sample used in this research was 93 respondents taken using purposive sampling techniques. The data used in this research is primary data with data collection methods using questionnaires distributed to respondents. The data analysis method uses Partial Least Square (PLS) via the SMART PLS application version 4.0. The results of this research show that: Tax Planning, Moral Obligations and Tax Audits have a positive and significant effect on Corporate Taxpayer Compliance. Digitalization of Tax Administration is able to moderate the influence of Tax Planning, Moral Obligations and Tax Audits on Corporate Taxpayer Compliance. It is hoped that the results of this research can be used as consideration for taxpayers to be aware of their contribution in paying taxes, and for tax authorities to continue to carry out evaluations to increase taxpayer compliance.